Role of calcination process of natural colemanite powder on compressive strength property of concrete - Nihat Utku Guner; Sezai Kutuk; Tuba Kutuk-Sert (Heliyon)
The use of boron minerals as an additive is important in terms of reducing CO2 emissions and providing input to the economy. Sustainable natural colemanite was subjected to calcination at 550 °C in order to concentrate the amount of B2O3. For the characterization of calcined mineral, XRD, TGA/DTA, and B2O3 component tests were carried out. It was observed that the structure of natural colemanite changed, and the B2O3 value heightened by 11 %. Then, natural and calcined minerals were added to the concrete mixture in proportions of 1.25 %, 2.5 %, 5 %, 7.5 %, 10 %, 12.5 %, and 15 % by weight. Ultrasonic pulse velocity, Schmidt hardness, and compressive strength tests were fulfilled. In the samples with natural additives, the lowest compressive strength was 32 MPa for the reference sample, whereas the highest strength was 44 MPa for the 10 % natural colemanite sample. In other words, the compressive strength increased by 39 %. In the samples with calcined additives, the highest compressive strength was 30 MPa for the 2.5 % calcined colemanite sample; that is, it improved by 24 %. It is realized that the cement can be saved since high strength can be obtained in concrete with natural and calcined colemanite additives.